What are digital English abbreviations? / Nor Haniza Hasan - Hasan, Nor Haniza (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
Digital English abbreviations, also known as internet slang or online shorthand, are abbreviations and acronyms commonly used in digital communication, such as text messages, social media, instant messaging, and online forums. These abbreviations often save time, space, and keystrokes and convey emotions, tone, or emphasis.